Early stage value co-creation network – business relationships connecting high-tech B2B actors and resources: Taiwan semiconductor business network case. Issue 4 (8th May 2018) - Park, Changhyun; Lee, Heesang
Abstract : Purpose: The purpose of this study is to identify the types and features of business relationship when the value co-creation phenomenon is extended to an early stage of the value chain, in which technological innovation is essential, in a high-tech business-to-business (B2B) market. Design/methodology/approach: The methodology of building a theory from a case study is adopted in this study to propose an early-stage value co-creation network. Qualitative data are coded on the basis of grounded theory coding after collecting the triangulation data from multiple sources. Findings: In a high-tech B2B market, three types of business relationships (supplier–customer mutual, supplier-centric and network-based business relationships) co-create values at an early stage of the value chain. Intellectual resource, efficiency resource and supplier-centric business relationships are uniquely found in this stage. Research limitations/implications: This study provides new insight suggesting that the notion of value co-creation can be extended to early stages of the value chain in a high-tech B2B market. In addition, this research identifies vital business relationships and how these relationships develop successfully at an early-stage value co-creation network in a high-tech B2B market. Practical implications: Technology development managers at an early stage of the value chain can co-create relationship benefits by building proposed business relationships integrating resources in a high-tech B2B market. In addition, marketing managers should consider the early stage as another source of value co-creation. Originality/value: The notion of value co-creation is extended from the later stage to an early stage of the value chain in a high-tech B2B market. Consolidated framework of a value co-creation network integrating actors, resources and relationships, suggested in this study, will be valuable for further theoretical research and business application.